Rip Van Winkle's republic : Washington Irving in history and memory - Burstein, Andrew; Isenberg, Nancy (Baton Rouge : Louisiana State University Press, 2022)
"In the twenty-first century, precious little has been written about America's first professional author, Washington Irving, who was one of the most well-known and highly esteemed writers of the nineteenth century. Rip Van Winkle's Republic marks a rediscovery and reassessment of this marvelous author of social satire and fabled tales of the past. It evaluates Irving's mind, his unique take on the human condition, and the new understandings of early US culture afforded by renewed study of his large body of work, with special attention to his international bestseller The Sketch Book (1819-1820), the collection of tales that included the immortal "Legend of Sleepy Hollow" and "Rip Van Winkle." Edited by two eminent historians of early America, Andrew Burstein and Nancy Isenberg, Rip Van Winkle's Republic approaches the author and his times from a variety of angles. The book is, first of all, interdisciplinary in character, its contributors a mix of professional historians and literary scholars. The foreword, introduction, and ten original essays interweave critical thoughts on the growth of an independent American idiom along with the growth of American literature in a transatlantic market; the place of the American Revolution and treatment of indigenous Americans and African Americans in nineteenth-century literature; and the fragility of memory and construction of historical memory more broadly. As a bibliophile and, definitively, an antiquarian, or lover of the archive, Irving belongs in discussions of book culture. This volume also emphasizes Irving as a prominent figure in an age of literary celebrity. More than one of the contributors examine his place in the history of American theater and in film and television adaptations of his work. Finally, given his iconic status throughout America's first 100 years as a nation, Rip Van Winkle's Republic queries his curious disappearance from the literary canon over the past half-century"--
Preface: Why Washington Irving still matters / Andrew Burstein -- Rites and times of the grand tour / Michelle Sizemore -- Washington Irving reimagined as father of his country / Shirley Samuels -- Reading The sketch book from its clattering hooves up / Nancy Isenberg -- Irving's relicts / Matthew Dennis -- Irving's investment in time / Alexis McCrossen and Andrew Burstein -- Tracing northern slavery in the Knickerbocker stories / Elizabeth L. Bradley -- A toast to, and distillation of, Rip Van Winkle / Tracy Hoffman -- The Revolutionary War lives on / Erik Weiselberg -- Irving Family manuscripts / Catalina Hannan -- An actor's reflections on the theatrical Irving / Curtis Armstrong.
Includes bibliographic references and index.
Description based on online resource; title from digital title page (viewed on September 21, 2022).
eBooks on EBSCOhost
Keywords: Irving, Washington, -- 1783-1859 -- Criticism and interpretation; Irving, Washington, -- 1783-1859.; Van Winkle, Rip -- (Fictitious character); Irving, Washington, -- 1783-1859; Sketch-book of Geoffrey Crayon, gent (Irving, Washington); American literature -- 1783-1850 -- History and criticism; Authors, American -- 19th century -- Biography; United States -- In literature; United States -- History -- 1783-1865.; Littérature américaine -- 1783-1850 -- Histoire et critique; Écrivains américains -- 19e siècle -- Biographies; États-Unis -- Histoire -- 1783-1865.; American literature; Authors, American; Literature; United States; 1783-1899; Electronic books; Biographies; Criticism, interpretation, etc; History